Characterization of parental intention to vaccinate elementary school aged children in the state of California. Issue 3 (16th January 2023) - Dudley, Matthew Z.; Barnett, Erin E.; Paulenich, Alex; Omer, Saad B.; Schuh, Holly; Proveaux, Tina M.; Buttenheim, Alison M.; Klein, Nicola P.; Delamater, Paul; McFadden, SarahAnn M.; Patel, Kavin M.; Salmon, Daniel A.
Abstract: In October 2021, Emergency Use Authorization of Coronavirus Disease 2019 (COVID-19) vaccines was granted for children aged 5–11. To ensure vaccine uptake in children upon approval, California will implement a state-wide executive order mandating COVID-19 vaccination for school children following full US FDA approval. This study uses survey data collected between November 6th, 2020 and December 14th, 2020 (n = 2091) to identify how sociodemographic characteristics and attitudes towards childhood vaccines among California parents were associated with their intentions to vaccinate their child against COVID-19. About one quarter (26 %) of surveyed California parents did not intend to vaccinate their child, suggesting skepticism towards the COVID-19 vaccine for children and the potential for pushback to a COVID-19 vaccine school-entry mandate. However, 17 % were unsure of their decision, suggesting the potential for public health messaging to make a positive impact on COVID-19 vaccine confidence and uptake. This study identifies characteristics of hesitant parents in California to prioritize for research and outreach. These data also provide a baseline for parental attitudes towards vaccinating children against COVID-19 in California, which will be useful for characterizing changes in attitudes towards childhood COVID-19 vaccination over time.